The artworks of Hasnul Jamal Saidon in projection: Interpretation through semiotic approaches - Kong, Hannah Nyuk Fun (2022)
This research is focused on an interpretation study of selected artworks of projection in new media art. In terms of intellectual characteristics of studies and knowledge of projection art, the situation in our nation regarding this new media development is lacking. The main aim of this research is to interpret the meaning of the images of projection artworks of Hasnul Jamal Saidon. Each of the artworks selected is scrutinized under the semiotics approaches of analysis by Charles Sanders Pierce (1977) which include constructing the content analysis semiology of the sign, object, and interpretant as well as in-depth interviews serving as key data collecting components. Aside from discovering signs and meanings in every component of the artworks, the research is also designed to uncover the value of the message that needs to be conveyed in Hasnul’s artworks in projection art. The research shows the reflection of new media and its ever-changing, complex modes of expression in Hasnul’s artworks where the perceived value of a rich context, perceptions, the knowledge of the natural world, and the values of the social, moral, and conventional world. The findings showed that Hasnul were able to describe the meaning, themes, and questions on his artworks that he tried to work on, appropriate to various situations and audiences at that time. Projection art should be given more attention in art field research in Malaysia.